Energy Transition Knowledge and Perceived Benefits among Households in Kpone-Katamanso Municipality, Ghana. (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This research was conducted to find out people’s satisfaction with the current energy situation in Kpone Katamanso Municipality and asses their willingness to transition to a more sustainable source of energy.Design/Methodology/Approach: Stratified sampling was employed to categorise the entire municipality into strata, facilitating data collection. A sample size of (100) respondents answered questionnaires administered to them. A 5-point Likert scale questionnaire was administered to individual respondents during the data collection.  Exploratory Factor analysis was done using both descriptive and bivariate analysis (the Pearson correlation method with a confidence level of 95% and a two-sided significance level of 5%).Research Limitation: The sampled survey covered only a section of the study population in Ghana. As such, the results cannot be generalised for the entire population of Ghana.Findings: It showed that awareness and knowledge, perceived benefits and costs, attitude, and motivation have a strong positive relationship with people’s willingness to shift to sustainable energy. Additionally, Kpone Katamanso Municipality is dissatisfied with the current energy situation and looks forward to transitioning to more sustainable energy sources, provided they are cost-effective.Practical Implication: This study on readiness for energy transition shows the willingness of the sampled population to accept energy transition. As such, if energy transition is implemented, it will enable Ghana to achieve a Net-Zero carbon economy by 2070.                                                                                                                           Social Implication: The demonstrated willingness for energy transition reveals emerging social consensus around environmental priorities, potentially strengthening community cohesion around sustainability goals and creating foundations for collective action on climate issues.Originality/ Value: The research identifies and categorises previously unexplored benefit perceptions unique to household contexts, including family security, domestic comfort, social status, and intergenerational considerations that influence energy transition decisions.
Keywords: Benefits. energy. knowledge. society. transition